Formation and Palaeozoic evolution of the Gorny-Altai–Altai-Mongolia suture zone (South Siberia): Zircon U/Pb constraints on the igneous record - Glorie S.; De Grave J.; Buslov M.M.; Zhimulev F.I.; Izmer A.; Vandoorne W.; Ryabinin A.; Van den haute P.; Vanhaecke F.; Elburg M.A. (My University, 2011)
The Altai-Sayan Fold Belt epitomises how Phanerozoic island-arc continental crust contributed to the growth of the Palaeo-Eurasian continent. Its formation is dominated by the closure of the Palaeo-Asian Ocean (PAO) when island-arc systems and Gondwana-derived terranes accreted to the Siberian margin. Relics of the PAO related tectonic units and associated granitoids occur along the ophiolitic Charysh–Terekta–Ulagan–Sayan suture (CTUSs) between Gorny-Altai and Altai-Mongolia. Zircon LA-ICP-MS U/Pb dating of this igneous record constrains themulti-stage geodynamic PAO evolution. Primitive Kuznetsk-Altai island-arc crust formed at the Siberian margin during the Ediacaran–Early Cambrian (525–555 Ma). This island-arc matured during the Middle–Late Cambrian (~510 Ma) and was consumed by PAO subduction in the Late Cambrian–Early Ordovician (480–490 Ma) forming the Siberian Early Caledonian accretion–collision belt. South of the CTUSs, granitic magmatism occurred within Gondwana-derived Altai-Mongolia during the Middle–Late Ordovician (450–470 Ma) Palaeo-Kazakhstan assembly and during a Silurian–Early Devonian (400–425 Ma) Andean-type collision. Middle–Late Devonian (360–395 Ma) granitoids were emplaced as a result of the collision of Altai-Mongolia with Siberia. During ﬁnal Pangaea amalgamation, the suture was strike-slip reactivated (associated magmatism ~295 Ma). The youngest (220–255 Ma) sampled granitoids originated in an intraplate setting.
Keywords: Gorny Altai; Charysh–Terekta–Ulagan–Sayan suture; Central Asian Orogenic Belt; Zircon LA-ICP-MS U/Pb geochronology; Phanerozoic continental growth; Paleozoic::Ordovician; Paleozoic::Cambrian; Палеозой::Кембрийская; Палеозой::Ордовикская